Gaze correction for videoconferencing - Ang, Billy Thiam Guan (2010)
A common tool in the area of visual communication would be the web cameras, used for capturing scene images that are to be streamed across the network. Yet, it is a common problem for any web camera to capture images that are offset to the gaze of the user, hence losing the eye-contact with the opposite party. By not maintaining eye contact, visual communication users may experience degrading effects and thus may not enjoy the true benefits from the technology.